Analysis and Implementation of PlayFair Chipper Algorithm in Text Data Encoding Process - Pristiwanto Pristiwanto; Heri Sunandar; Berto Nadeak (Jurnal Info Sains : Informatika dan Sains, 2020)
This research discusses the implementation of Playfair Cipher to encode text data. Playfair Cipher is one of the classic cryptographic algorithms that use symmetry keys. Originally invented by Sir Charles Wheatstone and Baron Lyon Playfair, the algorithm used a 5x5 keyboard to encrypt and decrypt. The process of encryption and decryption is done by grouping the letters in a bigram. By using a 5x5 keyboard, we can encrypt plaintext (original text data to be encrypted) and decrypt the ciphertext (encrypted text data) by grouping it by removing the letter J from plaintext. The keypad is generated randomly by the software so that each encoding process (encryption and decryption) can use different keys. The software is also used to prove the correctness of the encryption and decryption results of the Playfair Cipher with cube keyboards. Cipher Playfair software is developed using the C++ language and is console-based in a Windows development environment.